m 6 A Modification Prevents Formation of Endogenous Double-Stranded RNAs and Deleterious Innate Immune Responses during Hematopoietic Development - Gao, Yimeng; Vasic, Radovan; Song, Yuanbin; Teng, Rhea; Liu, Chengyang; Gbyli, Rana; Biancon, Giulia; Nelakanti, Raman; Lobben, Kirsten; Kudo, Eriko; Liu, Wei; Ardasheva, Anastasia; et al. (Immunity (Cambridge, Mass.), 2020)
N -methyladenosine (m A) is the most abundant RNA modification, but little is known about its role in mammalian hematopoietic development. Here, we show that conditional deletion of the m A writer METTL3 in murine fetal liver resulted in hematopoietic failure and perinatal lethality. Loss of METTL3 and m A activated an aberrant innate immune response, mediated by the formation of endogenous double-stranded RNAs (dsRNAs). The aberrantly formed dsRNAs were long, highly m A modified in their native state, characterized by low folding energies, and predominantly protein coding. We identified coinciding activation of pattern recognition receptor pathways normally tasked with the detection of foreign dsRNAs. Disruption of the aberrant immune response via abrogation of downstream Mavs or Rnasel signaling partially rescued the observed hematopoietic defects in METTL3-deficient cells in vitro and in vivo. Our results suggest that m A modification protects against endogenous dsRNA formation and a deleterious innate immune response during mammalian hematopoietic development.